The Recalibration of a Design Studio Curriculum During Covid–19 in Aotearoa - Ellis, Meighan; Grieve, Fiona (Universidade Anhembi Morumbi, 2021)
This article presents the impact COVID–19 had on a first-year communication design curricula revitalisation to progress students from a secondary level standards-based criterion to a tertiary culture predicated on active and experiential practice-led studio inquiry. Methodologically, it describes a design-based research intervention that asks what occurred in the translation of a brief written as an in-person, studio-based model into a purely online undertaking, learning from anywhere, teaching in a constant state of flux? Through a commentary on practice, the revitalisation of a design programme, and the pedagogical shift from within the traditional studio paradigm–a dynamic on-campus, in-person model into an abrupt and atypical online undertaking due to the global pandemic, this paper contributes to a discourse on a design studio approach and presents the transference of the Learning Management System that supports distance learning.
Keywords: COVID–19; Curriculum Design; Design Education; Online Learning; Studio Practice